Determinants of weekly sitting time: construct validation of an initial COM-B model and comparison of its predictive validity with the Theory of Planned Behaviour. Issue 1 (2nd January 2021) - Howlett, Neil; Schulz, Joerg; Trivedi, Daksha; Troop, Nicholas; Chater, Angel
Abstract: Objective: In relation to sitting behaviour, to investigate which theoretical domains best formed the Capability, Opportunity, and Motivation constructs of the COM-B, and compare the predictive validity to the Theory of Planned Behaviour (TPB), taking habit strength into consideration. Design: Using a prospective design, 186 adults completed measures capturing domains from the Theoretical Domains Framework for the three COM-B constructs, and habit strength, which were examined using a formative measurement model. Predictive validity was then compared to the TPB. Main Outcome Measures: Self-reported sitting behaviour. Results: Self-monitoring (behavioural regulation domain) formed Capability; subjective norm (social influences domain) formed Opportunity; intention (intentions domain), positive affect (emotion domain), and perceived behavioural control (beliefs about capabilities domain), formed Motivation. The COM-B strongly predicted sitting behaviour (27% variance explained), with Capability, Opportunity, and habit strength as key drivers. The TPB explained a large amount of variance (23%) in sitting behaviour, with intention and habit strength as key drivers. Conclusions: The behavioural regulation domain of Capability, the social influences domain of Opportunity, and habit strength were important drivers of sitting behaviour, with comparable variance predicted in the COM-B and TPB. Future research should consider this approach to conceptualise the COM-B for specific populations and behaviours.